PenetaPan Hadis sebagai HujjaH dalam menjawab isu-isu KontemPorer (studi Pada bahtsul masail muktamar nu Ke-33 tahun 2015) - Armita, Pipin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
Hadis is one of reference to solve problems that arise in contemporary society issues. Likewise conducted by Nahdhatul Ulama (NU) on Bahtsul Masail Muktamar NU 33th 2015. Th interesting thing is how does NU positioning hadis as a proof (hujjah) to deciding religion contamporary issues in the Bahtsul Masail. So, this paper aims to how determination Hadith as one of proofin Bahtsul Masail on Muktamar NU 33th 2015 and what methods is used by NU to determine that hadith as a proof. Ths reseach using archaeological approach to analyse the problems what carried by Foucalt on power and knowledge relation theory. Base on this theory, truth must be conceived as a system ofprocedures to regulate the production, regulation, distribution, circulation, and operation statements. As the result, author found that on Bahtsul Masail Muktamar NU 33th 2015 there are 13 themes that include hadis as a proof either either directly through the book ofHadith or Fiqh book, book oftafsir, and others.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />